Off-label dermatologic uses of IL-23 inhibitors - Justin Porter; Lacey Zimmerman; Melissa Nickles; Sheryl Hoyer (Journal of Dermatological Treatment)
Background While IL-23 inhibitors, which include guselkumab, tildrakizumab, and risankizumab, are currently FDA-approved solely for the treatment of psoriasis, several other inflammatory skin conditions have been associated with elevated IL-23 levels. The purpose of this review is to summarize and interpret the literature surrounding the off-label uses of IL-23 inhibitors in dermatologic practice.Methods We conducted searches on PubMed and ClinicalTrials.gov for clinical trials, observational studies, case series, and case reports assessing use of the three IL-23 inhibitors for non-psoriatic dermatologic conditions.Results Conditions exhibiting promising response to treatment with IL-23 inhibitors include hidradenitis suppurativa, lichen planus, pityriasis rubra pilaris, pyoderma gangrenosum, dissecting cellulitis of the scalp, congenital ichthyosiform erythroderma, lichen planus pemphigoides, acrofacial vitiligo, lichen planopilaris, frontal fibrosing alopecia, lupus erythematosus tumidus, and Stewart-Treves angiosarcoma.Conclusion Current literature suggests that IL-23 inhibitors may be effective in treating these conditions due to shared pathophysiologic pathways with psoriasis. Although these results are promising, further research through large-scale, randomized clinical trials is needed to further evaluate the efficacy and safety of IL-23 inhibitors in treating these off-label conditions.